Bridewell Legal Advice Study (BLAST): an innovation in police station legal advice: interim report - Kemp, Vicky (Legal Services Research Centre, 2012)
The Bridewell Legal Advice Study (BLAST) was an innovative project which attempted to help improve access to legal advice by basing duty solicitors in a large city centre police station. It had been intended that the project would run over a three month period but one of the main barriers to improving access to legal advice identified was poor relations between the police and the defence. Accordingly, the finding arising out of this first phase of the study was published as an Interim Report. The issues examined include the take-up of legal advice, the length of time people are held in custody and case outcomes. Also explored are some of the reasons why suspects decline legal advice, changing relations between the police and the defence, implications for police performance targets on policing strategies and decision-making as well as the role of police station legal advisers. A second phase of the project went ahead and the findings are reported in a final report.